Facilitated long chain fatty acid uptake by adipocytes remains upregulated relative to BMI for more than a year after major bariatric surgical weight loss. (20th November 2015) - Ge, Fengxia; Walewski, José L.; Torghabeh, Mehyar Hefazi; Lobdell, Harrison; Hu, Chunguang; Zhou, Shengli; Dakin, Gregory; Pomp, Alfons; Bessler, Marc; Schrope, Beth; Ude‐Welcome, Aku; Inabnet, William B.; et al.
Abstract : Objective: This study examined whether changes in adipocyte long chain fatty acid (LCFA) uptake kinetics explain the weight regain increasingly observed following bariatric surgery. Methods: Three groups (10 patients each) were studied: patients without obesity (NO: BMI 24.2 ± 2.3 kg m −2 ); patients with obesity (O: BMI 49.8 ± 11.9); and patients classified as super‐obese (SO: BMI 62.6 ± 2.8). NO patients underwent omental and subcutaneous fat biopsies during clinically indicated abdominal surgeries; O were biopsied during bariatric surgery, and SO during both a sleeve gastrectomy and at another bariatric operation 16 ± 2 months later, after losing 113 ± 13 lbs. Adipocyte sizes and [ 3 H]‐LCFA uptake kinetics were determined in all biopsies. Results: V max for facilitated LCFA uptake by omental adipocytes increased exponentially from 5.1 ± 0.95 to 21.3 ± 3.20 to 68.7 ± 9.45 pmol/sec/50, 000 cells in NO, O, and SO patients, respectively, correlating with BMI ( r  = 0.99, P  < 0.001). Subcutaneous results were virtually identical. By the second operation, the mean BMI (SO patients) fell significantly ( P  < 0.01) to 44.4 ± 2.4 kg m −2, similar to the O group. However, V max (40.6 ± 11.5) in this weight‐reduced group remained ∼2X that predicted from the BMI: V max regression among NO, O, and SO patients. Conclusions: Facilitated adipocyte LCFA uptake remains significantly upregulated ≥1 year after bariatric surgery, possibly contributing to weight regain.